DNA Repair Pathway in Ovarian Cancer Patients Treated with HIPEC - Flasarova, Dominika; Urban, Katerina; Strouhal, Ondrej; Klos, Dusan; Lemstrova, Radmila; Dvorak, Pavel; Soucek, Pavel; Mohelnikova-Duchonova, Beatrice (International journal of molecular sciences, 2023)
DNA repair pathways are essential for maintaining genome stability, and understanding the regulation of these mechanisms may help in the design of new strategies for treatments, the prevention of platinum-based chemoresistance, and the prolongation of overall patient survival not only with respect to ovarian cancer. The role of hyperthermic intraperitoneal chemotherapy (HIPEC) together with cytoreductive surgery (CRS) and adjuvant systemic chemotherapy is receiving more interest in ovarian cancer (OC) treatment because of the typical peritoneal spread of the disease. The aim of our study was to compare the expression level of 84 genes involved in the DNA repair pathway in tumors and the paired peritoneal metastasis tissue of patients treated with CRS/platinum-based HIPEC with respect to overall patient survival, presence of peritoneal carcinomatosis, treatment response, and alterations in the BRCA1 and BRCA2 genes. Tumors and metastatic tissue from 28 ovarian cancer patients collected during cytoreductive surgery before HIPEC with cisplatin were used for RNA isolation and subsequent cDNA synthesis. Quantitative real-time PCR followed. The most interesting findings of our study are undoubtedly the gene interactions among the genes CCNH, XPA, SLK, RAD51C, XPA, NEIL1, and ATR for primary tumor tissue and ATM, ATR, BRCA2, CDK7, MSH2, MUTYH, POLB, and XRCC4 for metastases. Another interesting finding is the correlation between gene expression and overall survival (OS), where a low expression correlates with a worse OS.
Keywords: DNA Glycosylases; HIPEC; Retrospective Studies; indukovaná hypertermie; Hyperthermic Intraperitoneal Chemotherapy; hypertermická intraperitoneální peroperační chemoterapie; míra přežití; nádory vaječníků; Hyperthermia, Induced; kombinovaná terapie; DNA-glykosylasy; Disease-Free Survival; ženské pohlaví; DNA repair; retrospektivní studie; Humans; oprava DNA; Survival Rate; Antineoplastic Combined Chemotherapy Protocols; ovarian cancer; Combined Modality Therapy; protokoly protinádorové kombinované chemoterapie; DNA Repair; Female; Ovarian Neoplasms; biomarkers; přežití bez známek nemoci; lidé